Global, regional, and national burden of epilepsy, 1990–2021: a systematic analysis for the Global Burden of Disease Study in 2021 - Tianqi Sun; Tianfu Yu; Pengcheng Liu (Cost Effectiveness and Resource Allocation)
Abstract Background Idiopathic epilepsy is a serious neurological disorder that can lead to premature death and severe disability. We aimed to assess the global burden of idiopathic epilepsy, to provide a comprehensive understanding of the current dynamics and trends in idiopathic epilepsy, and to gain insight into its epidemiological attributes. Methods This study assessed the global, regional, and national impact of idiopathic epilepsy through incidence and disability-adjusted life year (DALY) based on the Global Burden of Disease Study 2021 (GBD 2021). After statistically summarizing the global incidence rates and disability-adjusted life years (DALYs), we performed Estimating Average Percent Change (EAPC) correlation analyses and Joinpoint regression analyses to further derive global trends in idiopathic epilepsy incidence rates and DALYs. Furthermore, through decomposition analysis, we determined which factors significantly influence the change in incidence and DALYs and the extent of their contribution. In addition, this study quantified the disparities in the burden of idiopathic epilepsy across countries through cross-country social inequality analyses, and finally predicted the future burden of idiopathic epilepsy based on Bayesian Age-Period-Cohort Model (BAPC). Results From 1990 to 2021, the incidence of idiopathic epilepsy increased generally, whereas DALY decreased. In terms of age and gender, the burden of idiopathic epilepsy is more severe in children and older age groups, with males bearing a higher burden than females. In terms of geographical distribution, the incidence was significantly higher in high Socio-Demographic Index (SDI) regions, while the burden of idiopathic epilepsy was heavier in low SDI areas. Decomposition analyses showed that the increase in incidence of idiopathic epilepsy and DALY in high SDI regions was mainly driven by epidemiological changes, whereas the increase in low SDI areas was more due to population growth. Cross-country social inequality analyses showed that despite improvements in the burden of idiopathic epilepsy, the burden and inequalities in low SDI countries remains significant. Projections indicated an increase in the incidence of idiopathic epilepsy globally, particularly in the 85 + age group, while global DALY was anticipated to continue declining. Conclusions Although global health is improving in line with population growth and age structure, the burden of idiopathic epilepsy remains significant. This study provides an important basis for prevention and care strategies for idiopathic epilepsy in different regions. Future work should focus on integrating idiopathic epilepsy into public health priorities, promoting effective measures, and narrowing treatment gaps.